Effect of multi‐frequency ultrasound surface washing treatments on Escherichia coli inactivation and some quality characteristics of non‐heading Chinese cabbage. Issue 10 (30th October 2018) - Alenyorege, Evans Adingba; Ma, Haile; Ayim, Ishmael; Zhou, Cunshan; Wu, Ping; Hong, Chen; Osae, Richard
Abstract : The effect of ultrasound washing with different frequencies including sweeping, fixed and combined fixed frequencies on Escherichia coli inactivation and selected physical and chemical qualities of Chinese cabbage were investigated. Colour, microstructure, total chlorophyll, total carotenes, total phenolic content, DPPH radical scavenging, hydroxyl radical scavenging and reducing power activities were measured using standard in vitro assays. In contrast with water washed samples, ultrasound washing with a fixed frequency of 40 kHz resulted in >3 log CFU/g reduction in E. coli counts, approximately 20% improvement in total phenolic content and over 32% increase in reducing power activity. There was, however, a marginal improvement in DPPH radical scavenging activity and a decrease in hydroxyl radical scavenging activity. Scanning electron micrographs revealed the presence of micro‐fractures and minute holes and dislodging of surface particles Ultrasound washing improved the perceptible visual colour (∆ E ) and the greenish appearance of the leaves. Practical applications: Multi‐frequency power ultrasound washing of fresh produce is a recent application of varying frequencies in decontamination of fresh produce. The remarkable influence of ultrasonic frequency aside other operating parameters in the removal of contaminants on fruits and vegetable surfaces influenced this study. The results reported in this experimental study may be considered for application in the inactivation of microorganisms including E. coli and other Gram‐negative bacteria. This washing technique may also be used in combination with other studied physical or chemical preservation methods as a synergy to enhance microbial removal and quality characteristics of fresh produce in the food industry.